(untitled) (Movimenta (ISSN 1984-4298), 2022)
The objective of the present work is to report the experience of the development of the University Extension Project “ReabilitArte”, including a brief history and the activities that have taken place since its creation, with adaptations resulting from the COVID-19 pandemic. Among the activities developed, the project rehabilitated patients with oral and maxillofacial mutilations, offering an improvement in their quality of life. For the training of students, theoretical and laboratory classes were given by the project coordinators. In addition, scientific articles were published, resulting from clinical case reports, literature reviews and laboratory research, as well as activities in digital media during the pandemic period. Thus, 45 maxillofacial prostheses were made; taught 1 theoretical class and 4 laboratory classes; 14 scientific articles were published; 2 Symposia and 34 posts were developed on the Instagram social network. In this way, the project disseminated knowledge about oral and maxillofacial prosthetic rehabilitation, in addition to benefiting the population with individualized clinical